Long-term evolution of CD4+ cell count in patients under combined antiretroviral therapy. (1st August 2019) - Pantazis, Nikos; Papastamopoulos, Vasilios; Paparizos, Vasilios; Metallidis, Simeon; Adamis, Georgios; Antoniadou, Anastasia; Psichogiou, Mina; Chini, Maria; Sambatakou, Helen; Sipsas, Nikolaos V.; Gogos, Charalambos; Chrysos, Georgios; et al.
Abstract : Objective: Combined antiretroviral treatment (cART) results in profound immunologic improvement, but it is unclear whether CD4 + cell counts return to levels similar to those of HIV-negative individuals. We explore long-term CD4 + cell count evolution post-cART and its association with baseline levels, virologic suppression, pre-cART cumulative viremia and other factors. Design: Data were derived from the AMACS. Included individuals were adults who started cART, at least 2003, while previously ART-naive. Methods: Changes in CD4 + cell counts were modeled through piecewise linear mixed models. Results: A total of 3405 individuals were included. The majority was male (86.0%), homosexual (58.8%) with median (IQR) age at cART initiation 36 (31–44) years and a median (IQR) follow-up of 3.9 (2.0–6.9) years. Most persons (57%) starting cART with less than 200 cells/μl did not reach 600 cells/μl after 7 years of treatment. Those starting cART with 200–349 CD4 + cells/μl could reach 600 cells/μl within less than 2 years of fully suppressive treatment. Probability of CD4 + normalization (i.e. >800 cells/μl) after 7 years of suppressive treatment was 24 and 46% for those starting treatment with less than 200 or 200–349 CD4 + cells/μl, respectively. Lower pre-cART cumulative viremia was associated with faster CD4 + recovery. CD4 + cell count increases after 4 years were either insignificant or very slow, irrespectively of baseline levels. Conclusion: cART initiation before CD4 + cell count drops below 350 cells/μl is crucial for achieving normal CD4 + levels. These findings underline the importance of timely diagnosis and cART initiation as the risk of both AIDS and non-AIDS-related morbidity/mortality remains increased in patients with incomplete CD4 + recovery.